Mathematics of program construction : 12th International Conference, MPC 2015, Königswinter, Germany, June 29-July 1, 2015. Proceedings /: 12th International Conference, MPC 2015, Königswinter, Germany, June 29-July 1, 2015. Proceedings. (2015) - Unknown
No abstract available